Continued change amongst the positive news for science - Stevens, Craig (New Zealand Science Review, 2016)
​ The 2016 Budget is good news for Investigator-led (Marsden Fund) and Health research, where additional support adds to well-evolved funding processes. Elsewhere, it looks like there will be continuing change for the New Zealand science system. The Marsden Fund, which supports investigator-led research will be increased and should see success rates exceed 10% in the next couple of years. NZAS President Craig Stevens says, ‘This is a positive signal for New Zealand’s fundamental research community, but we see a need to get closer to 15-20% success rates to really provide an engine for the nation’. This increase, combined with the boost to health research already signalled, will efficiently increase research productivity in these areas. Elsewhere the budget shows how the government is implementing its National Statement of Science Investment (NSSI). The Innovative New Zealand initiative looks to restructure a number of aspects of how science in New Zealand is funded including contestable funding and support for large, nationally significant components of the research sector. Stevens says ‘we hope that the Innovative NZ initiative sticks with the NSSI itself and supports impact in the environment and society sectors, and not just research with direct immediate economic return. Science is often about the long-game. ‘The Endeavour Fund repackages the MBIE contestable fund with some additional support, although the additional funds appear to be compensating for an earlier redirection of funding to the National Science Challenges. Stevens says ‘we are relieved the Government has seen that the MBIE process needs to be improved, as we have real concerns about this funding model in terms of efficiency and process.’ Stevens says, ‘We hope these changes put scientists in the centre of decision making’. For example, The Catalyst Fund seeking to strengthen international collaborations is proving to be a complex, highly prescribed process. On the whole I think New Zealand scientists are really good at building international links and you have to wonder if the laudable NSSI goals in this area might be achieved simply by better supporting scientists and let them naturally build these collaborations.’ Of concern is the budget signal of uncertainty for CRI science and scientists, as what was known as Core Funding evolves into the Strategic Science Investment Fund. Stevens says ‘It is positive that the government sees that key elements within the New Zealand science system need to be handled in particular ways. We’ll need to wait and see how the Strategic Science Investment Fund is rolled out before we fully understand the impact.’